EVALUASI PENGGUNAAN OBAT ANTIHIPERTENSI PADA PASIEN HIPERTENSI DI INSTALASI RAWAT JALAN RUMAH SAKIT UMUM BHAKTI ASIH CILEDUG PERIODE OKTOBER-DESEMBER 2021 - Suny Koswara Suny (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2023)
Hypertension is an increase in systolic blood pressure exceeding 140 mmHg and diastolic blood pressure exceeding 90 mmHg in two measurements with an interval of five minutes in a state of sufficient rest or calm (Kemenkes, 2019). The purpose of this study was to determine the rationale for the use of antihypertensive drugs in hypertensive patients at the Outpatient Installation of Bhakti Asih General Hospital, Ciledug, October-December 2021. This study used a descriptive design with retrospective data collection. The data used in this study were medical record sheets of hypertension patients at Bhakti Asih General Hospital Ciledug for the period October-December 2021 with a Cross Sectional approach. This study used a simple random sampling technique and obtained 165 patients who met the inclusion criteria. Based on the results of the study, it is known that the characteristics of adult hypertensive patients based on age are the most elderly age >60 years, namely 95 patients (57.57%) and based on gender the most are women as many as 103 patients (62.42%). The most used class of drugs was the CCB group 69 patients (41.81%), the antihypertensive group that the single therapy was mostly used was 103 patients (66.43%), and the group of combination drugs used was the CCB+ARB group 48 patients ( 29.09%). Evaluation of rational drug prescribing on each criterion, namely 100% Right Patient, 100% Right Indication, 100% Right Drug, 97.58% Right Dose.